Three-dimensional Voronoi-based distinct element model for simulation of hydraulic fracture propagation - Ghazvinian, E; Kalenchuk, KS (Deep Mining 2017: Proceedings of the Eighth International Conference on Deep and High Stress Mining, 2017)
Hydraulic fracturing is a complex physical process which involves the coupling of hydraulic and mechanical behaviours as well as, in some cases, temperature effects. The interdependence of these various factors is complex, and cannot be fully captured by the relatively simple state-of-practice tools employed in investigations of hydraulic fracturing. In this paper, a new approach is presented for fully coupled hydromechanical simulation of hydraulic fracture propagation by using three-dimensional Voronoi geometries within the context of distinct element formulation. The block boundaries formed by the Voronoi tessellation, providing a random flow pathway for the fluid and the contact breakage due to the increase of the fluid pressure acting on them, replicate the hydraulic fracture propagation. While the Voronoi approach for hydraulic fracturing simulation has been implemented previously in 2D models, this work puts forward a technique for extension of its application to 3D models. A series of verification tests are performed to investigate the suitability of the proposed approach. Finally, example applications are presented for simulation of single-stage and multi-stage hydraulic fracturing of intact rock by using the 3D Voronoi models at large scale.
Keywords: numerical modelling